Contraction-Associated Maternal Heart Rate Decelerations: A Pragmatic Marker of Intrapartum Volume Status. Issue 4 (October 2018) - Lappen, Justin R.; Chien, Edward K.; Mercer, Brian M.
Abstract : OBJECTIVE: To define and characterize a maternal contraction-associated heart rate deceleration pattern and evaluate its association with maternal volume status. METHODS: We performed a prespecified secondary analysis of a prospectively collected cohort from a randomized controlled trial of maternal pulse pressure, epidural coload volume, and postepidural complications. Participants were healthy intrapartum women with nonanomalous singleton gestations at 35 weeks of gestation or greater and a category 1 fetal heart rate (FHR) pattern from admission to epidural placement. Those lacking continuous maternal pulse oximetry data before epidural placement were excluded. Maternal heart rate tracings were evaluated for the presence of a contraction-associated heart rate deceleration pattern before epidural placement. Women with and without a contraction-associated heart rate deceleration pattern were compared using univariable and multivariable analyses. The primary outcome was the frequency of a contraction-associated heart rate deceleration pattern in hypovolemic compared with euvolemic women as defined by admission pulse pressure (less than 45 and 50 mm Hg or greater, respectively). Secondary outcomes included the association of a contraction-associated heart rate deceleration pattern with postepidural complications related to maternal volume status including new-onset category 2 and 3 FHR abnormalities, maternal hypotension, and the need for resuscitative obstetric interventions. RESULTS: Of 414 trial participants, 388 (93.7%) met inclusion criteria, and 124 of these (32.0%) had a contraction-associated heart rate deceleration pattern before epidural placement. The presence of a contraction-associated heart rate deceleration pattern was more frequent among hypovolemic compared with euvolemic women as defined by admission pulse pressure (41.1% vs 13.6%, relative risk [RR] 3.0, 95% CI 1.9–4.8, P <.001). A contraction-associated heart rate deceleration pattern was associated with more frequent postepidural FHR abnormalities (43.5% vs 31.1%, RR 1.4, 95% CI 1.1–1.8, P =.02), diastolic hypotension (63.7% vs 50.0%, RR 1.3, 95% CI 1.1–1.5, P =.01), and the need for resuscitative interventions (33.9% vs 23.1%, RR 1.5, 95% CI 1.1–2.0, P =.03). In multivariable analysis with adjustment for baseline differences between groups, the associations between a contraction-associated heart rate deceleration pattern and abnormal FHR patterns, diastolic hypotension, and the need for resuscitative interventions persisted and were slightly strengthened. CONCLUSION: The maternal contraction-associated heart rate deceleration pattern is a pragmatic, bedside visual indicator of intrapartum maternal volume status. A contraction-associated heart rate deceleration pattern is threefold more frequent among hypovolemic compared with euvolemic women as defined by admission pulse pressure and is associated with postepidural complications including abnormal FHR patterns, diastolic hypotension, and the need for resuscitative interventions. The contraction-associated heart rate deceleration pattern highlights a novel role for intrapartum maternal heart rate assessment and may inform the individualization of intrapartum fluid management. Abstract : The maternal contraction-associated heart rate deceleration pattern is a pragmatic, bedside visual indicator of maternal volume status and highlights a novel role for intrapartum maternal heart rate assessment.